Carbon dioxide removal efficiency of iron and steel slag in seawater via ocean alkalinity enhancement - Moras, Charly A.; Joannes-Boyau, Renaud; Bach, Lennart T.; Cyronak, Tyler; Schulz, Kai G. (Frontiers in Climate, 2024)
Ocean alkalinity enhancement (OAE) via the enhanced weathering of alkaline minerals is a promising carbon dioxide removal (CDR) technology. Theoretically, these includes iron and steel slags, although their dissolution kinetics in seawater are unknown. Here, we conducted lab-scale experiments to assess the alkalinity generation potential and dissolution kinetics of various slags in seawater. We show that the alkalinity generated per mass of iron slag was logarithmic, i.e., higher amounts of iron slag added had diminishing alkalinity returns. In contrast, the relatively quick dissolution of steel slags and their linear generation of alkalinity per mass of feedstock dissolved in seawater makes them better OAE candidates. Furthermore, despite the presence of potentially toxic metals in these feedstocks, their low to non-existent presence as dissolution products suggests that harmful concentrations should not be reached, at least for the slag tested here. Finally, if all steel slag produced annually was used for OAE, between 10 and 22 gigatonnes of CO2 could be captured cumulatively by 2,100, highlighting significant CDR potential by slags.